Neuropathic Pain - Macone, Amanda; Otis, James A. D. (Seminars in Neurology, 2018)
Neuropathic pain management is challenging, and typically requires a multifaceted approach. There are several treatment options, both pharmacologic and nonpharmacologic. Of the available pharmacologic agents, those with the strongest supporting evidence include tricyclic antidepressants, serotonin–norepinephrine reuptake inhibitors, and certain antiseizure agents. There is emerging evidence for the use of cannabinoids, but conclusive studies are not available. Nonpharmacologic therapies that have been utilized in the management of neuropathic pain include acupuncture, massage therapy, and reflexology. Despite their use as adjunctive therapies in clinical practice, the current evidence supporting their use is not strong. For the management of neuropathic pain, combination therapies are generally employed. Additional studies for emerging therapies are still needed.
Keywords: tricyclics; cannabinoids; ketamine; acupuncture